International business/ Oded Shenkar, Yadong Luo and Tailan Chi - Shenkar, Oded; Luo, Yadong; Chi, Tailan (Routledge, 2022)
This fully revised and updated fourth edition offers an action-focused, practical approach to the topic, helping students understand the global business environment and its repercussions for executives. The book provides thorough coverage, delving into fundamental concepts and theory; the cultural, political, and economic environment; international business strategies; and even functional management areas.